Phylogeography of Rotavirus G8P[8] Detected in Argentina: Evidence of Transpacific Dissemination - Degiuseppe, Juan Ignacio (2022)
Rotavirus is one of the leading causes of diarrhea in children. In 2018, G8P[8], an unusual association of genotypes, was detected with moderate frequency in symptomatic children in Argen-tina, unlike a previous sporadic identification in 2016. The aim of this study was to analyze the dissemination pattern of the G8P[8]-lineage IV strains detected in Argentina. Nucleotide sequences of the VP7 gene of Argentine G8P[8] strains (2016, 2018 and 2019) were studied by discrete phylodynamic analyses, together with other worldwide relevant G8-lineage IV strains. Bayes Factor (BF) was used to assess the strength of the epidemiological association between countries. Phylodynamic analyses determined an evolutionary rate of 3.7 × 10−3 (HDP95%: 1.4 × 10−3–8.2 × 10−3) substitutions/site/year. Likewise, the most recent common ancestor was 32.2 years old, dating back to 1986 (HDP95% = 1984–1988). The spatiotemporal dynamics analysis revealed South Korea as being the country of origin of the Argentine strains (posterior probability of the ancestral state: 0.8471), which was also evidenced by a significant rate of diffusion from South Korea to Argentina (BF: 55.1). The detection of G8 in South America in 2016–2017 was not related to the cases detected in 2018–2019, revealing a new G8 introduction to the region and supporting a transpacific dissemination.